Capital, Governance, and Power: How Political Ties Influence Firm Value - Martino Wibowo; Harry Pambudi; Lela Nurlaela Wati; Sahraman Hadji Latif (Universitas Muhammadiyah Yogyakarta, 2025)
This study aims to determine the influence of political connection and its role in moderating the influence of capital structure and corporate governance on a firm’s value. The study was conducted on 97 samples of companies listed on the Indonesia Stock Exchange from 2020-2024 that were established about 10 years old or more, collected from various types of industrial sectors, with limitations on the criteria of ownership of political officials or political party officials (politically connected), family ownership who also serves as political officials (politically connected), pure ownership of businessman families (not politically connected), and central and/or regional government ownership (politically connected). The study used random sampling and panel data from the moderating regression analysis to examine the relationship between political connection, capital structure, and DAR proxy on a firm's value. A significant positive relationship between these factors and Tobin's Q was found. However, there was a negative association between political connection-moderated DAR and Tobin's Q. The study also uncovered a negative relationship between board size and the proportion of independent commissioners, but a positive relationship between board size and political connection. The study's novelty is that it fills the literature gap, investigating how the influence of capital structure and governance, moderated through political connections, affects the firm’s value, which other studies have not exhaustively studied.